The impact of medical insurance on family financial support: evidence from CHARLS in China - Cao, Yuan; Chen, Hua; Yang, Xiaoxu (Health economics review, 2023)
Background In China, public medical insurance has expanded rapidly in the past 20 years. Many studies have discussed the benefits of medical insurance in improving residents’ health and financial stability, and increasing the utilization of medical services. Less attention is paid to the effect of medical insurance on family support between parents and children. This study focuses on the effect of medical insurance on promoting family financial support in China. Method Fifty-five thousand sixty-two individual samples were obtained from four waves of the China Health and Retirement Longitudinal Study (CHARLS): 2011, 2013, 2015 and 2018. Linear-regression model and propensity score matching are used to determine the relationship between medical insurance and family financial support. Then, mediation model is introduced to identify the mediation mechanisms. Also, moderation model is used to estimate the moderation effect of parental education and health. Results Medical insurance has significantly increased family financial support between the insured parents and their children. Moreover, this positive effect is heterogeneous since only families living in rural areas were affected, and the direction of family financial support changed with the aging of the parents. The welfare of medical insurance on financial status have also been proven in this paper. The results indicate that medical insurance reduces the out-of-pocket ratio of medical expenses and increases health investment, which can perform as as two mediation mechanisms to affect family financial support. Besides, the education and health status of the insured parents play a role in moderating the effect of medical insurance.